Konsumsi Kalsium Mencegah Kejadian Preeklamsia - Evy Kasanova (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Preeclampsia is a midwifery problem that has become one of the leading causes of death besides bleeding and infection. Calcium consumption is one program to meet pregnant women’s calcium needs and prevent preeclampsia during pregnancy. They determined the effect of calcium consumption on preeclampsia incidence in the Working Areas of Menteng Public Health Center and Kereng Bangkirai Public Health Center. This was analytical observational research with a prospective cohort design. The research sample was 88 pregnant women in the 2nd and 3rd trimesters. The instrument for collecting the women’s basic data was an observational sheet. The number of tables consumed was a medication compliance card, and stress and anxiety levels were measured by DASS 42. Blood pressure was measured using a sphygmomanometer, mercury, and dan protein in urine using a urine glucose protein test. The data analysis was performed descriptively using chi-square and logistic regression. Calcium consumption affected preeclampsia incidence with a P-value of 0.012 RR 0.025. Calcium consumption affects preeclampsia incidence.